Health Care Reform in the USA - Zemanová, Iva (2011)
This thesis is concerned with US health care. It is focused especially on the health insurance market. It introduces basic characteristics of the US insurance system and discusses its main problems. The goal of this thesis is to determine whether voluntary private insurance is the main source of problems that the US health care system currently experiences. In order to do that, greatest deficiencies of US insurance policies, especially private ones, are identified based on the efficiency criterion. It is also briefly evaluated if identified deficiencies are going to be affected by the current health care reform.